Camouflage and Ballooning in Health Insurance: Evidence from Abortion - Julia Kathleen Neumann; Peter Zweifel; Annette Hofmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper provides a microeconomic basis for simultaneously explaining two phenomena related to health insurance: camouflage and ballooning. We use abortions in Switzerland as an illustrative example. First, a significant share of abortions is camouflaged by contrived medical coding, and second, there is evidence of ballooning in that jurisdictions with strict enforcement of abortion regulation tend to export the problem to more liberal ones. The analysis differs from the existing literature in that we explicitly model the search effort of an individual seeking a health service, i.e., an abortion or camouflage. Using data provided by a major social health insurer, theoretical predictions are confirmed to a considerable degree. In particular, women who derive a particularly high benefit from an abortion (and even more so, from its camouflage) are less discouraged by strict enforcement than others.
Keywords: I18; J13; K42; 330